A Dixmier's theorem for finite type representations of amenable semigroups - Fack, Thierry (MATHEMATICA SCANDINAVICA, 2003)
Let $S$ be an amenable locally compact semigroup. We give ergodic and spectral characterizations of the finite type representations of $S$ that are unitarizable.